BMI as a Predictor for Potential Difficult Tracheal Intubation in Males - Uribe, Alberto A.; Zvara, David A.; Puente, Erika G.; Otey, Andrew J.; Zhang, Jianying; Bergese, Sergio D. (Frontiers in Medicine, 2015)
Introduction: Difficult tracheal intubation is a common source of mortality and morbidity in surgical and critical care settings. The incidence reported of difficult tracheal intubation is 0.1 to 13% and reaches 14% in the obese population. The objective of our retrospective study was to investigate and compare the utility of BMI as indicator of difficult tracheal intubation in males and females. Material and methods: We performed a retrospective chart review of patients who underwent abdominal surgeries with ASA I to V under general anesthesia requiring endotracheal intubation. The following information was obtained from medical records for analysis: gender, age, height, weight, BMI, length of patient stay in the Post Anesthesia Care Unit (PACU), past medical history of sleep apnea, Mallampati score, and the ASA classification assigned by the anesthesia care provider performing the endotracheal intubation. Results: Of 4303 adult patients, 1970 (45.8%) men and 2333 (54.2%) women, were enrolled in the study. Within this group, a total of 1673 (38.9%) patients were morbidly obese. The average age of the study group was 51.4 ± 15.8 and the average BMI was 29.7 ± 8.2 kg/m². The overall incidence of the encountered difficult intubations was 5.23%, or 225 subjects. Thus, our results indicate that BMI is a reliable predictor of difficult tracheal intubation predominantly in the male population; another strong predictor, with a positive linear correlation, being the Mallampati score. Conclusions: In conclusion, our data shows that BMI is a reliable indicator of potential difficult tracheal intubation only in male surgical patients.